Effectiveness of Neem Leaf Extract And Packaging Types On The Quality of Cilembu Variety Sweet Potato - Tazkia Mega Aulya; Putra Rizky Nugraha; Tety Suciaty1 (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Proper postharvest handling is a critical factor in maintaining the quality of sweet potatoes (Ipomoea batatas L). This research evaluated the effectiveness of neem leaf (Azadirachta indica A. Juss) extract concentration and packaging type in inhibiting sprouting, reducing infestation by the sweet potato weevil (Cylas formicarius), and maintaining weight loss, starch content, and total dissolved solids in Cilembu variety sweet potatoes during storage. This experiment used a Completely Randomized Design with three replications, consisting of neem extract concentrations (0, 10, 20 ml/L) and packaging types (jute sacks, polinet nets, bamboo baskets). Neem leaves contain azadirachtin compounds which can preserve the physiological quality of sweet potatoes from pest attacks. The higher the concentration, the higher the level of effectiveness in maintaining and preserving the physiological quality of sweet potatoes during storage therefore, this study tested neem leaf extract concentrations of (0, 10, 20 ml/L). Results showed that the combination of 10 ml/L and 20 ml/L neem leaf extract with poly-net packaging yielded the best overall quality. This treatment significantly reduced sweet potato weevil infestation by up to 99.4% and suppressed weight loss by up to 33.8%, while maintaining more stable starch content and total soluble solids. The 10 ml/L and 20 ml/L neem leaf extract demonstrated optimal insecticidal properties, while the poly-net packaging provided the best ventilation for releasing respiratory heat and controlling moisture accumulation compared to jute sacks and bamboo baskets. In conclusion, the combination of 10 ml/L and 20 ml/L neem leaf extract with poly-net packaging is effective in maintaining the quality of Cilembu variety sweet potatoes during storage.